Portable mobile surveillance and detection - Foo, Francis Patrick Canlas Phan Shan (2015)
With a rapid rate of obsolescence, smartphones are set to contribute significantly to the amount of electronic waste (e-waste) generated worldwide. With recycling as one of the key strategies to alleviate the situation, using old smartphones as surveillance cameras is one of the viable options that consumers can choose. The top three Android Surveillance applications in Google Play, at the point of writing, do not allow consumers the flexibility to perform clandestine legitimate surveillance and to manage their surveillance content beyond a smartphone. The Surveillance software suite developed in this project provides consumers the ability to remotely command their Mobile Surveillance Devices via Short Message Service (SMS), to capture photos and videos of the environment under surveillance clandestinely, by not displaying any previews. Consumers will also be able to manage the surveillance information through a Client Web Application, which can be accessed through supported browsers on electronic devices beyond the smartphone.